Prophylactic effects of Clausena excavata Burum. f. leaf extract in ethanol-induced gastric ulcers - Albaayit, Shaymaa Fadhel Abbas; Abba, Yusuf; Abdullah, Rasedee; Abdullah, Noorlidah (Dove Medical Press, 2016)
Clausena excavata is a natural herb with both antioxidant and anti-inflammatory properties. It has been used for decades in folkloric practice for the amelioration of various ailments. In this study, the gastroprotective activity of methanolic extract of C. excavata leaves (MECE) was determined in the Sprague Dawley rat ethanol-induced gastric ulcer model. Rats were pretreated with a single dose of vehicle (5% Tween 20), 20 mg/mL omeprazole, 400 and 200 mg/mL of MECE dissolved in 5% Tween 20. Ulcer was induced with 5 mL/kg of ethanol and stomach tissue was obtained after 1 hour. Histological examination was done on hematoxylin and eosin, periodic acid-Schiff, and immunochemically stained gastric mucosal tissues. Prostaglandin E2, superoxide dismutase, catalase, glutathione peroxidase, and lipid peroxidation levels of the gastric tissue homogenates were also determined. Significantly (P<0.05) smaller ulcer areas, less intense edema, and fewer leukocytes’ infiltration were observed in MECE- and omeprazole-treated than in untreated gastric mucosa with ulcer. The gastric pH, mucus production, superoxide dismutase, catalase, and glutathione peroxidase contents increased, while the lipid peroxidation content decreased as a result of MECE treatment. Bcl-2-associated X protein was underexpressed, while heat shock protein 70 and transforming growth factor-beta protein were overexpressed in the ulcerated gastric mucosa tissues treated with omeprazole and MECE. Similarly, there was a reduction in the levels of tumor necrotic factor-alpha and interleukin-6, while the level of interleukin-10 was increased. This study showed that the gastroprotective effect of MECE is achieved through inhibition of gastric juice secretion and ulcer lesion development, stimulation of mucus secretion, elevation of gastric pH, reduction of reactive oxygen species production, inhibition of apoptosis in the gastric mucosa, and modulation of inflammatory cytokines.